DAMPAK PANDEMI COVID-19 TERHADAP PENDAPATAN NELAYAN UDANG REBON DI SUKOLILO BARU SURABAYA - Evaningtyas Putri Windiawati; Anna Marina; Fitri Nuraini; Halimatus Sa'diyah (PROCEEDING UMSURABAYA, 2022)
A COVID-19 pandemic occurred in Indonesia in early March 2020, precisely after the discovery of 2 people cases who were identified as being exposed to the COVID-19 virus. COVID-19 was first discovered in Wuhan, China. The rapid spread had resulted in almost the entire world being affected by the pandemic. The impact that was felt the most is the economic sector. The research purpose determined the impact of the COVID -19 pandemic on the income of Rebon Shrimp fishermen in Sukolilo Baru Surabaya before and during the pandemic. This research approach used the Qualitative Phenomenology method because the researcher looked at the phenomena that occurred during the COVID-19 pandemic. The result found the highest percentage of income ratio obtained by fishermen was 77%. The impact of the pandemic showed that in a drastic drop in income. The provision, socialization, and training of fishermen's mothers and fathers can greatly help them to stabilize the economy. Innovations and ideas that can be developed for the acqu isition of rebon shrimp, for example made into shrimp paste, shredded rebon shrimp, and others can become big business opportunities for fishermen in Sukolilo Baru.Keywords: Income, Impact of the COVID-19 Pandemic, Comparison.